2008
DOI: 10.1093/molehr/gan054
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of pregnancy-associated plasma protein-A2 in the serum of pre-eclamptic patients

Abstract: Pregnancy-associated plasma protein-A and -A2 (PAPP-A and -A2) are proteases that cleave insulin-like growth factor-binding proteins (IGFBPs), resulting in local activation of IGF signaling pathways. Here, we examined PAPP-A and -A2 mRNA and protein levels in placenta and maternal sera from women with pre-eclampsia and compared them with samples from uncomplicated pregnancy. PAPP-A2 but not PAPP-A mRNA and protein were elevated in pre-eclamptic placenta (P < 0.01). PAPP-A2 is normally produced in placental syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
82
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(92 citation statements)
references
References 26 publications
7
82
3
Order By: Relevance
“…Several previous studies have published data indicating that PAPPA2 is increased in PE (Buimer et al 2008;Sitras et al 2009;Várkonyi et al 2010;Wagner and Christians 2010). In addition, PAPPA2 has also been localised to the syncytiotrophoblast previously (Nishizawa et al 2008;Wagner and Christians 2010) in both PE and PT placentas.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Several previous studies have published data indicating that PAPPA2 is increased in PE (Buimer et al 2008;Sitras et al 2009;Várkonyi et al 2010;Wagner and Christians 2010). In addition, PAPPA2 has also been localised to the syncytiotrophoblast previously (Nishizawa et al 2008;Wagner and Christians 2010) in both PE and PT placentas.…”
Section: Discussionmentioning
confidence: 87%
“…Nishizawa et al (2008) previously assessed PAPPA2 immunohistochemistry in term control (but not preterm) and severe early onset PE placentas and also suggested a decrease in PAPPA2 in control samples compared with PE. However, the present study appears to be the first to comprehensively compare PAPPA2 immunohistochemistry between PT, PE and term samples and to observe a lack of staining in term samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike PAPPA, which proteolyses both IGFBP4 and IGFBP5 (Boldt et al 2004), PAPPA2 cleaves IGFBP5 and may also show lower proteolytic activity against IGFBP3 (Overgaard et al 2001). Although the physiological functions of PAPPA2 have not been studied, at least four recent studies have found PAPPA2 to be upregulated in hypertensive disorders of pregnancy including preeclampsia and hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome (Buimer et al 2008, Nishizawa et al 2008, Sitras et al 2009, Winn et al 2009.…”
Section: Introductionmentioning
confidence: 99%